Model Komunikasi dan Strategi Dakwah Akun Youtube Aya Ibrahim - Ahmad Nurfajrin; Chodidjah Makarim; Fahmi Irfani (Universitas Pahlawan Tuanku Tambusai, 2023)
Communication models and dawah strategies are closely related concepts in the context of the development and dissemination of religious teachings. A communication model refers to the methods and approaches used to communicate with the audience or target audience, while dawah strategies refer to the techniques employed to convey religious messages to others. In communication models, there are several approaches that can be used to effectively communicate with the audience, allowing for meaningful dialogue and mutual respect. Dawah strategies can be categorized into various types. In practice, the use of communication models and dawah strategies can be tailored to the needs and characteristics of the intended audience. Therefore, it is important for dawah propagators to have adequate knowledge of both concepts in order to choose the most suitable models and strategies for delivering religious messages. Keywords: Communication models, Da’wah strategi, youtube chanel.